Novo modelo eletromagnético no domínio do tempo para cálculo da resposta de sistemas elétricos frente a descargas atmosféricas - Bárbara Pereira Silva (2021)
The aim of the dissertation consists in the development and test the formulation of an original model in the time domain, dedicated to the solution of problems related to the lightning effects on electric systems, that explores the electromagnetic coupling approach adopted in the Hybrid Electromagnetic Model (HEM), developed in the frequency domain. The proposed model can be able to problems involving nonlinear effects, such as soil ionization, the corona effect and the use of surge-arrester in transmission lines. For electrical groundings, the formulation in the time domain characterizes the fundamental parameters, notably concerning the propagation velocity of current and their attenuation along grounding electrodes. The frequency dependence of the soil parameters can also be considered by means an approximation. In evaluating the response of transmission lines to lightning discharges, a resource for impedance matching was developed, that allows investigating part of the system to be modeled in order to reduce the computational effort. For the purpose of illustrating the potential of the developed tool, it was applied to a set of conditions of practical interest in engineering, particularly the response of grounding subjected to first and subsequent discharge currents, including the ionization effect, and the response of lines transmission in view of the incidence of discharges, contemplating, in this case, the presence of the corona effect and surge arresters.